The Self-Efficacy Level Among Musically Talented Students (Al-Academy, 2023)
This Study Aimed to Recognize the Self-Efficacy Level Among Musically Talented Students the sample of this study consisted of (85) Musically smart students male and female students in Irbid governorate, of the analytical descriptive method ، and the Self-Efficacy scale were used, and the results indicated the following:-The Self-Efficacy level among Musically smart students was high.-There are no statistically significant differences (α ≥ 0.05)due to the impact of gender in a the total degree .-There are no statistically significant differences (α=0.05) due to the impact of stage in a the total degree.